Premature mortality from cardiovascular disease: global burden and country-specific estimate through review study, trend analysis, prediction modelling, and causal inference study - Hasani, Wan Shakira Rodzlan (2024)
Cardiovascular disease (CVD) is a leading cause of premature mortality worldwide, with its burden growing in recent years. Despite considerable research into CVD, there are noticeable gaps in addressing premature mortality associated with it. For example, there is insufficient information on global research activity and pool estimation of the global burden of premature CVD mortality from existing literature. Additionally, within-country estimates of this burden and country-specific CVD risk profiles are lacking. Therefore, this thesis aims to comprehensively analyze and understand various aspects of premature CVD mortality, including global research activities, estimating the global burden of CVD related to premature mortality, examining country-specific trends and risk profiles for premature CVD mortality, and constructing causal pathways for premature CVD mortality. This thesis consists of five interrelated studies aimed at addressing all research objectives. The first study summarizes the global publication information related to premature mortality through bibliometric analysis. The bibliometric analysis shows that premature mortality research has increased substantially in the past decade; however, there have been disparities in research output between high-income countries (HICs) and low-middle-income countries (LMICs), emphasizing the need for collaborative efforts in LMICs. In the second study, consisting of two parts: Study 2a, a systematic review concentrating on premature CVD mortality using the Years of Life Lost (YLL) indicator, followed by study 2b, a subsequent meta-analysis based on the age-standardized mortality rate (ASMR) indicator. Studies 2a and 2b underscore the persistent burden of premature CVD mortality, particularly in LMICs and among men, emphasizing the importance of targeted interventions and public health strategies. The third study involves trend analysis utilizing Malaysia country-specific mortality data from Dapartment of Statistics Malaysia employing a joinpoint regression model. This study reveals a persistent increasing trend of premature CVD mortality rates in Malaysia over the past decades, underscoring the ongoing burden in the country. In study four, a modeling study is conducted to assess the premature CVD risk profile by applying various survival models. This study utilizes data from Malaysia's National Health and Morbidity Survey (NHMS) conducted in 2006, 2011, and 2015, linked with mortality records through 2021. The semi-parametric and parametric survival models both highlight the considerable impact of socioeconomic status and modifiable risk factors on premature CVD mortality in Malaysia. Finally, the fifth study entails a causal inference study systematically demonstrating the construction of a Directed Acyclic Graph (DAG) model for premature CVD mortality. This study introduces a new approach integrating evidence synthesis and expert opinion using the Fuzzy Delphi method to construct the DAG model, followed by testing the model with available data. This step demonstrates a step-by-step process for constructing a causal model, offering a systematic, practical, and transparent approach, contributing to DAG methodology. In summary, through meticulous methodologies, the findings of this thesis contribute to the growing body of literature on premature mortality from CVD and provide valuable insights and frameworks for informing public health strategies and guiding future research endeavours in tackling premature CVD mortality.